Perbaikan Nilai CBR Tanah Lempung Lunak Dengan Stabilitas Dua Tahap dengan Menggunakan Abu Vulkanik - Yusrizal Lubis; Diana Suita (Universitas Harapan Medan, 2020)
Soil with unfavorable characteristics often creates new problems, one of which is soft clay. Therefore, a soil improvement method is needed to change the characteristics of the soil. Two-stage stabilization using bukho rock ash and volcanic ash has the potential to overcome this problem. Based on the results of the study, the optimum CBR value was 9.245% from two-stage stabilization of soft clay soils with 12% bukho rock ash and 4% volcanic ash added. The addition of 6% bukho rock ash and 4% volcanic ash obtained 100% soil density. The addition of 9% bukho rock ash and 4% volcanic ash obtained 100% soil density. The addition of 12% bukho rock ash and 4% volcanic ash obtained 100% soil density. This shows that the effect of two-stage stabilization based on percentage variations can increase soil density.